Pemanfaatan Karbon Baggase Teraktivasi Untuk Menurunkan Kadar Logam Tembaga Pada Limbah Kerajinan Perak Di Lombok Tengah - Indah, Dahlia Rosma; Safnowandi, Safnowandi (Hydrogen: Jurnal Kependidikan Kimia, 2018)
Copper metal levels in silver craft waste can cause health problems in humansand pollute the surrounding environment. One method of processing wastewateris the adsorption technique using activated carbon dioxide. The first step is tofirst determine the copper metal content in silver handicraft waste in UnggaVillage, Central Lombok. Furthermore, the waste water is contacted withactivated carbon. The production of activated bagasse carbon consists of threestages, namely first dehydration by burning bagasse until it turns into carbon,second carbonation which is heating temperature of 500ºC, carbon yields of 100-200 mesh and third, activation by immersing 50 grams of carbon in 500 mL 15%NaOH during 12 hours. After that the carbon is dried at 110ºC and finally heatedat 500ºC for 1 hour. The bagasse carbon that has been made is put into 25 mL ofwaste water sample with a mass of 2 grams of adsorbent. The sample is thenstirred at various contact times of 30, 60, 90, 120 and 150 minutes at a speed of180 rpm using a batch system. The optimum contact time and concentration areused to calculate the efficiency of decreasing copper metal content by calculatingthe difference in copper metal content before adsorption and after adsorptionusing activated carbon dioxide. The concentration of all Cu (II) metals wasanalyzed using Atomic Absorption Spectrophotometer (AAS). From the researchit was found that the copper metal content in the sample was 14.5710 ppm. Theoptimum contact time for copper metal adsorption is at 120 minutes contact timewhich results in optimum adsorption efficiency in ferrous metals, namely84.88%.